When workplace ostracism leads to burnout: the roles of job self-determination and future time orientation. Issue 17 (25th September 2019) - Qian, Jing; Yang, Fu; Wang, Bin; Huang, Chuying; Song, Baihe
Abstract: Given that ostracism is a common occurrence in the workplace, scholars and practitioners alike have identified its range of negative effects. This study aims to examine the association between workplace ostracism and burnout level as well as the moderating effects of job self-determination and employees' future time orientation, using a survey questionnaire. This was completed by a total of 248 employees from a hotel group. We hypothesized that: (a) workplace ostracism was positively associated with burnout; (b) this positive relationship was contingent upon job self-determination such that the relationship was weaker for higher, rather than lower, job self-determination; and (c) the positive relationship was also contingent upon employees' future time orientation such that the relationship was weaker for employees who have higher, rather than lower future time orientation. Results confirm all three hypotheses.